Nervous System of Periplaneta americana Cockroach as a Model in Toxinological Studies: A Short Historical and Actual View - Maria Stankiewicz; Marcin Dąbrowski; Maria Elena de Lima (Journal of Toxicology)
Nervous system of Periplaneta americana cockroach is used in a wide range of pharmacological studies, including electrophysiological techniques. This paper presents its role as a preparation in the development of toxinological studies in the following electrophysiological methods: double-oil-gap technique on isolated giant axon, patch-clamp on DUM (dorsal unpaired median) neurons, microelectrode technique in situ conditions on axon in connective and DUM neurons in ganglion, and single-fiber oil-gap technique on last abdominal ganglion synapse. At the end the application of cockroach synaptosomal preparation is mentioned.